PENGARUH KONSELING GIZI SEIMBANG DENGAN BUKU SAKU TERHADAP PERILAKU IBU, POLA MAKAN SERTA TINGKAT KONSUMSI ENERGI DAN PROTEIN BADUTA STUNTING - Ratri Puspitasari; I Dewa Nyoman Supariasa; Astutik Pudjirahaju; AAG Anom Aswin (Poltekkes Kemenkes Malang, 2019)
The results of the baseline data in Sumberngepoh Village, Lawang Sub District, Malang Regency on 10 until 15 April 2017 reported that out of 96 toddlers, 38 toddlers or 39.5 percent had stunting nutritional status. The purpose of this study was to analyze the effect of balanced nutrition counseling on pocket books on maternal behavior, dietary patterns and energy and protein consumption levels of stunted children under two in Sumberngepoh Village, Lawang Subdistrict, Malang Regency. The research method used pre experimental design with one group pretest posttest design. This research was conducted on 30 June until 19 August 2018 in mother stunted children under two in Sumberngepoh Village, Lawang Subdistrict, Malang Regency. The study population was all mothers who had children under two with short and very short nutritional status of 13 people. The sample of the study was mothers who had children under two with short and very short nutritional status of 10 people. The sampling technique used in the study was purposive sampling. The results showed that balanced nutrition counseling with pocket books had a significant influence on maternal behavior namely knowledge, attitude and practice with each p equal 0.005, p equal 0,000 and p equal 0.038. Balanced nutrition counseling with pocket books has no significant effect on the dietary patterns namely p equal 0.554 and the level of energy consumption namely p equal 0.312 and the level of protein consumption namely 0.444 of stunted children under two. The need for the provision of routine nutrition counseling on balanced nutrition is appropriate for children aged 6 until 24 months and provides assistance to those who are stunted